Adhemar Gonzaga e a Cinédia: imagens de um país que dança - Suzana Cristina de Souza Ferreira (2006)
It was in the final of the 1920's and the 1930's that Adhemar Gonzaga started playing himself another role into the history of the Brazilian Cinema. From that date on he did not only write and lead campaigns for the Cinema in the press, mainly in Cinearte, a cinema journal conceived and created by him in 1926: he made Cinema. With the construction of the Studio Cinedia, the most ambitious of his projects, Gonzaga materialized the means to accomplish his cultural sthetical project for the Brazilian Cinema.A project oriented by an ideal of modernity, of nationalism, of development and, although that would seem as an incoherence, by the North American model ofmaking Cinema. Adhemar Gonzaga and the ideas whichoriented that project are the objects of study of this thesis.